Chasing the light : improving your photography with available light - Perello, Ibarionex (Voices that matter., 2011)
Light. It's the most powerful tool that any photography has at their disposal. Whether the lens is turned to people, wildlife or the landscape, it is often the creative use of light that transforms a snapshot into a photograph. Chasing the Light will enlighten photographers of all levels and help them make the most of this most important tool--light. With over 25 years of experience in the photographic industry as a photographer, writer, and educator, Ibarionex Parello has developed an approach to photography that has helped photography enthusiasts from all over the world discover and nurture their own passion for photography. In Chasing the Light, he brings his palpable passion to the subject as he guides the reader through many scenarios--landscape, action, portraits--using his principle of the "Three Qs" (Quantity, Quality, and Qolor). Utilizing a very personal approach rooted in decades of experience, he shares how to see, control, and use available light to create beautiful and impactful photographs. By developing the way photographers "see" light, Chasing the Light aids them to make the connection between the camera and their own eye; and the buttons and dials that control focus, exposure, white balance, and sharpness. In an industry so filled with obsessions about gear, Chasing the Light removes much of that from the discussion and returns the reader to a basic, yet inspirational, conversation about leveraging light to take evocative photographs.